# Math

posted by .

solve using the substitution method. If the system has no solution or infinite number of solution state this
4x+4y=-36
4x+4y=12

• Math -

4x + 4y = -36
-4x -4x

4y = -4x-36
/4 /4 /4

y = -x-9
Now you substitute this equation into the second one.

4x + 4(-x-9)= 12
Distribute the 4
4x-4x = -36
0x = -36
0 is not equal to -36, so that means this has no solution.

## Similar Questions

1. ### Algebra

Solve using the substitution method. Show your work. If the system has no solution or an infinite number of solutions, state this. x + 10y = 41 x + 9y = 37
2. ### algebra

Solve using the substitution method. Show your work. If the system has no solution or an infinite number of solutions, state this. x + 10y = 41 x + 9y = 37
3. ### Algebra

Solve using the substitution method. If the system has no solution or an infinite number of solutions, state this. -x + 6y = 54 3x + y = 9
4. ### math

Solve using the substitution method. If the system has no solution or an infinite number of solutions, state this. -2x + 0y = -14 x + 11y = 18
5. ### math

Solve using the substitution method. Show your work. If the system has no solution or an infinite number of solutions, state this. 8y + 2x = 48 2x = 4y – 12
6. ### Algebra

Solve using the substitution method. Show your work. If the system has no solution or an infinite number of solutions, state this: 4x + 4y = -36, 4x + 4y = 12
7. ### Algebra

Solve using the substitution method. Show your work. If the system has no solution or an infinite number of solutions, state this. 4x + 4y = -36 4x + 4y = 12
8. ### Algebra

Solve using the substitution method. Show your work. If the system has no solution or an infinite number of solutions, state this. 4x + 4y = -36 4x + 4y = 12
9. ### algebra

Solve using the substitution method. Show your work. If the system has no solution or an infinite number of solutions, state this. 4x + 4y = -36 4x + 4y = 12
10. ### algebra

Solve using the substitution method. Show your work. If the system has no solution or an infinite number of solutions, state this. 3x – 15y = -12 3x + 24y = -12

More Similar Questions